Optimizing product design and development of engine carbon cleaning maintenance tools using reverse engineering and VDI 2222 methods - Wijaya, Dewa Kusuma; Hartono, B.J Ridwan; Jazuli, Jazuli; Izzhati, Dwi Nurul (OPSI, 2024)
This research article explains the product design and development optimization of multi feature engine carbon cleaning maintenance tools. The implementation of the Reverse Engineering method was integrated with VDI 2222 in the research process. The results of the optimal design and development of this tool obtained a component structure that was able to meet 14 types of consumer needs with a total tool cost of IDR 1.137.900 with a total tool weight of 6.9 kg. The results of the load test simulation concluded that the housing case was able to withstand the overall weight of the components that make up the tool. Depending on the liquid chemical used, the results of tool tests on a limited scale have proven to be able in save fuel consumption by ±12.5% per hour with engine workload which can also be reduced by 3,14%.